Letter : Deputation to Foreign Minister - Marchbank, John
012a-0107-001 TELEGRAMS BEWARE NORWEST LONDON TELEPHONE EUSTON 4771 five lines The National Union of Railwaymen Unity House Euston Road London N.W.1 J. Marchbank General Secretary. G. W. Brown, Assistant General Secretary Your ref In your reply refer to G.S/1001/3. 5th April, 1938. Sir Walter Citrine, K.B.E., General Secretary, T.U.C. General Council, Transport House, Smith Square, S.W.1. Dear Sir Walter, DEPUTATION TO FOREIGN MINISTER. I wish to acknowledge receipt of your letter of the 4th instant notifying the members of the General Council that a meeting will be held at your office at 4. o'clock before proceeding to an interview with Lord Halifax to take place at the Foreign Office at 4.30p.m. tomorrow. Unfortunately I have a meeting of the London & Home Counties Traffic Advisory Committee at 4. o'clock but I will do my best to be present with the deputation. Yours sincerely, John Marchbank 292/946/12a/107